Democracy, education, and difference: against the current of neoliberal and neoconservative policies (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2024)
In this article, an analysis of the neoliberal and neoconservative hegemonic alliance in the global social, political and economic field is carried out, which also generates strong impacts on education. The aim is to encourage thinking around possible articulations between democracy, education and difference, based on the operationalization of concepts developed by Ernesto Laclau, Chantal Mouffe and Judith Butler. It is understood that policies are produced in conflicting and antagonistic power relations between differential demands. The neoliberal and neoconservative hegemonic alliance arises from the articulation between these differential demands that become equivalent and begin to form the constitutive interior of the established order. Within it, social demands advocating for justice and the right to education are not considered, making them the constitutive exterior of this political game. This is the discursive production of democracy interrelated with education and difference as a totality serving the neoliberal and neoconservative alliance of the capitalist system. However, any totality will always be partial, precarious, and contingent. The challenge posed would be to think about radical democracy, open to different demands, which, in the game of political disputes, remain as the constitutive exterior of the hegemonic project. This is because radical democracy allows to understand and create other chains of equivalences that can project and dispute counter-hegemonic struggles more forcefully.Keywords: Democracy. Difference. Education.